2019
DOI: 10.1002/app.48598
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and thermal performances of epoxy resin/graphitic carbon nitride composites

Abstract: In this paper, a series of graphitic carbon nitride (g-C 3 N 4 ) was synthesized under different thermal oxidation etching temperatures and epoxy/g-C 3 N 4 composites were prepared via solution blending. The morphology and structure of g-C 3 N 4 were investigated by transmission electron microscope, X-ray diffraction (XRD), Fourier transform infrared spectroscopy, and X-ray photoelectron spectroscopy. The tensile fracture morphology and structure of epoxy resin (EP) composites were demonstrated by scanning ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
(38 reference statements)
0
13
0
Order By: Relevance
“…However, at 0.5 wt% filler loading, 21.7% and 8% improvement in tensile strength and modulus were achieved. It can be assumed that the presence of ─NH 2 and ─NH groups in g‐C 3 N 4 form strong interactions with the hydroxy and epoxide groups of the resin, leading to this enhancement in properties 1 . When the wt% of g‐C 3 N 4 was further increased to 0.75, 1, and 2 wt%, the strength dropped to as low as 22.92 ± 3.7 MPa, even lower than the value of pure epoxy.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, at 0.5 wt% filler loading, 21.7% and 8% improvement in tensile strength and modulus were achieved. It can be assumed that the presence of ─NH 2 and ─NH groups in g‐C 3 N 4 form strong interactions with the hydroxy and epoxide groups of the resin, leading to this enhancement in properties 1 . When the wt% of g‐C 3 N 4 was further increased to 0.75, 1, and 2 wt%, the strength dropped to as low as 22.92 ± 3.7 MPa, even lower than the value of pure epoxy.…”
Section: Resultsmentioning
confidence: 99%
“…The study also showed that this interaction could lead to better load transfer between the components of the composite 18 . Most recently, Qi et al 1 attempted to reinforced epoxy resin with g‐C 3 N 4 synthesized at different etching temperatures. They were able to successfully improve the tensile strength of epoxy by 58% and delay its degradation temperature by 21.5°C.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The second is carbonaceous materials (graphene 18 and carbon 19 ). The third is ceramic particles (SiO 2, 20 SiC, 21 and BN 22 ). Conductor and semiconductor can significantly improve the thermal conductivity of EP but reduce the electrical resistivity and electrical properties of the material 23 .…”
Section: Introductionmentioning
confidence: 99%